Superoxide-responsive fluorogenic molecular probes for optical bioimaging of neurodegenerative events in Alzheimer's disease - Shin, Jawon; Kang, Dong Min; Yoo, Jounghyun; Heo, Jeongyun; Jeong, Keunsoo; Chung, Ji Hyung; Han, Ye Sun; Kim, Sehoon (Royal Society of Chemistry, 2021)
Since oxidative stress has been recognized as a major factor contributing to the progression of several neurodegenerative disorders, reactive oxygen species (ROS) including superoxide have received great attention as a representative molecular marker for the diagnosis of Alzheimer's disease (AD). Here, superoxide-sensitive fluorogenic molecular probes, benzenesulfonylated resorufin derivatives (BSRs), were newly devised for optical bioimaging of oxidative events in neurodegenerative processes. BSRs, fluorescence-quenched benzenesulfonylated derivatives of resorufin, were designed to recover their fluorescence upon exposure to superoxide through a selective nucleophilic uncaging reaction of the benzenesulfonyl cage. Among BSRs, BSR6 presented the best sensitivity and selectivity to superoxide likely due to the optimal reactivity matching between the nucleophilicity of superoxide and its electrophilicity ascribed to the highly electron-withdrawing pentafluoro-substitution on the benzenesulfonyl cage. Fluorescence imaging of inflammatory cells and animal models presented the potential of BSR6 for optical sensing of superoxide in vitro and in vivo. Furthermore, microglial cell (Bv2) imaging with BSR6 enabled the optical monitoring of intracellular oxidative events upon treatment with an oxidative stimulus (amyloid beta, A beta) or the byproduct of oxidative stress (4-hydroxynonenal, HNE).
Keywords: LIPID-PEROXIDATION; HYDROGEN-SULFIDE; SELECTIVE DETECTION; NEURONAL APOPTOSIS; NLRP3 INFLAMMASOME; OXIDATIVE STRESS; PATHOGENESIS; BRAIN; PRODUCT; DYSFUNCTION